Effective Possibilities of Applying Pedagogical Educational Innovations - Azamat Ruzvonovich Rakhmonov (Academia One Publishing, 2023)
The implementation of innovations in the field of education is considered to depend on innovations and is expressed in modern concepts. Therefore, the article tried to reveal the possibilities of using pedagogical innovations.
Keywords: Science and educational innovation; researchers of innovative processes